Síntese, caracterização e deposição sobre óxido de grafeno de nanopartículas de óxido de índio dopado com estanho (ITO) - Firmiano, Edney Geraldo da Silveira (2011)
In this study, in the first step, Indium tin oxide nanoparticles were synthesized via a non-aqueous route involving the solvothermal treatment of indium (III) acetylacetonate and tin (IV) chloride in polyethylene glycol Mw=1000. The use of microwave heating reduced the reaction time considerably when compared to traditional heating methods. An analysis by transmission electron microscopy (TEM) revealed particles of relatively uniform sizes and shapes. The high crystallinity of the material was observed by high resolution transmission electron microscopy (HRTEM). The nanocristal size founded by count was 5,1nm. A powder X-ray diffraction analysis indicated that all the materials were crystalline. Infrared spectra confirmed the presence of organic material on the nanoparticle surface. By thermogravimetric analysis (TGA) determined that 11.3% of the total mass corresponds to the polymer. Resistivity values below 10-1 Ω.cm were obtained in thin films and pellets, and semiconductor behavior. In the second step, a model to control the covered area of graphene oxide (GO) sheets by ITO nanoparticles was proposed. The method used was add graphene oxide at the synthetic route to obtain pure ITO. The composites were characterized by XRD, FT-IR, TGA and TEM. XRD results for the synthesized materials confirmed the diffraction patterns of ITO in the different composites synthesized. Through the analysis of FT-IR was possible confirm the presence of the polymer formed on the surface of the oxide nanoparticle and functional groups of graphene oxide sheets. The polymer attached on the oxide surface is responsible for the strong interaction between the ITO and graphen oxide sheets. TEM images for the samples with different cover percentage showed the controller achieved with the synthesis proposed. The composite with 100 or 10% of metal oxides covering the sheets surface did not show the presence of nanocrystals out sheets. The percent value of the covered area obtained of 15% founded by image J analisys is near to the calculated value. From this value we can say that the model works well to control the covered area of GO by nanocristals. The electrical resistivity values found are comparable to the pure ITO, however, with a smaller amount of ITO.